Development of physics e-module based on integrated project-based learning model with Ethno-STEM approach on smartphones for senior high school students - Yulkifli Yulkifli; Yohandri Yohandri; Hasbi Azis (Universitas PGRI Kanjuruhan Malang, 2022)
Standard competency of graduate students of class XI in Physics learning is considered not optimal. One of the contributing factors is the unavailability of the Physics E-Module, which contains model steps and is integrated with a learning approach in order to direct students in active learning. This study aims to produce a Physics E-Module based on an integrated project-based learning model with an Ethno-STEM approach on smartphones for class XI high school students with valid, practical, and effective criteria. This is development research using the Plomp development model consisting of three stages: Preliminary Research, Development or Prototyping Phase, and Assessment Phase. The instruments used in this research include three questionnaires for preliminary study, validity and practicality, attitude observation sheets, written test sheets, and skills assessment sheets. The result obtained was a Physics E-Module based on an integrated project-based learning model with the Ethno-STEM approach on smartphones for class XI high school students who meet valid, practical, and effective criteria.